Mechanistic Analysis of Nonoxygenated Hypothermic Machine Perfusion's Protection on Warm Ischemic Kidney Uncovers Greater eNOS Phosphorylation and Vasodilation. Issue 11 (10th October 2014) - Chatauret, N.; Coudroy, R.; Delpech, P. O.; Vandebrouck, C.; Hosni, S.; Scepi, M.; Hauet, T.
<x xml:space="preserve">Abstract</x> Protection of endothelial cell function may explain the benefits of nonoxygenated hypothermic machine perfusion (MP) for marginal kidney preservation. However, this hypothesis remains to be tested with a preclinical model. We postulated that MP protects the nitric oxide (NO) signaling pathway, altered by static cold storage (CS), and improves renal circulation recovery compared to CS. The endothelium releases the vasodilator NO in response to flow via either increased endothelial NO synthase (eNOS) expression (KLF2‐dependent) or activation of eNOS by phosphorylation (via Akt, PKA or AMPK). Using a porcine model of kidney transplantation, including 1 h of warm ischemia and preserved 24 h by CS or MP (n = 5), we reported that MP did not alter the cortical levels of KLF2 and eNOS at the end of preservation, but significantly increased eNOS activating phosphorylation compared to CS. eNOS phosphorylation appeared AMPK‐dependent and was concomitant to an increased NO‐dependent vasodilation of renal arteries measured, ex situ, at the end of preservation. In vivo, laser Doppler showed that cortical microcirculation was improved at reperfusion in MP kidneys. In conclusion, we demonstrate for the first time, in a large‐animal model, that MP protects the NO signaling pathway, confirming the value of MP for marginal kidney preservation.